DOI: 10.22215/etd/2022-15318
|View full text |Cite
|
Sign up to set email alerts
|

Daily Order of Alcohol and Cannabis Use Predicts Drinking Quantity on Simultaneous Use Days, but Substance Use Motives do not Moderate

Abstract: The present study examined whether using alcohol versus cannabis first when simultaneously using predicts levels of alcohol consumption on a given day, while focusing on daily levels of coping and enhancement motives for simultaneous alcohol and cannabis (SAM) use. Undergraduate student drinkers (n=370) participated in a 14weekend diary study in Fall 2021, completing surveys on Friday, Saturday, and Sunday mornings (n=2,826 responses) assessing their SAM use, alcohol consumption, and motives for SAM use the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
(182 reference statements)
0
1
0
Order By: Relevance
“…In contrast, Schulenberg and colleagues (2019) found that 8.3% of young adults in their U.S. study used cannabis daily or nearly-daily. Although the main eligibility criterion for enrollment in the present study was alcohol use (e.g., using alcohol at least two to three times per month), only 40.5% of alcohol use days included cannabis use (Carnrite, 2022). A recent study examining college students from seven countries found that over 75% partake in simultaneous alcohol and cannabis use (Bravo et al, 2021).…”
Section: Cannabis Use Frequencymentioning
confidence: 85%
“…In contrast, Schulenberg and colleagues (2019) found that 8.3% of young adults in their U.S. study used cannabis daily or nearly-daily. Although the main eligibility criterion for enrollment in the present study was alcohol use (e.g., using alcohol at least two to three times per month), only 40.5% of alcohol use days included cannabis use (Carnrite, 2022). A recent study examining college students from seven countries found that over 75% partake in simultaneous alcohol and cannabis use (Bravo et al, 2021).…”
Section: Cannabis Use Frequencymentioning
confidence: 85%